PENGEMBANGAN SUMBER DAYA MANUSIA PENYULUH KEHUTANAN DAN KELOMPOK TANI HUTAN PADA CABANG DINAS KEHUTANAN WILAYAH MALANG - Angguliyah; Sinollah; Majid, Syahrul (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2022)
Forests are natural resources that provide many benefits, both directly and indirectly. Forest utilization and forest preservation are very important for the sustainability of life, therefore the use and conservation of forests must be balanced. In forest conservation, the government must be proactive and act as a driving force and as the main forest protector. In addition to the government, the community must also play an active role in preserving and reforesting forests (reforestation). The government has established a forestry service whose task is to maintain the sustainability and sustainability of the forest. Forestry extension workers and forest farmer groups must know the regulations related to forest areas and management. The existence of forestry extension workers and forest farmer groups will not be effective if the capacity and knowledge of human resource development on forestry are not fulfilled. Human resource development is a continuous effort to improve the quality of human resources in the broadest sense, through education, training, and coaching (Silalahi, 2000: 249). Thus, these efforts can be increased using the On-The-Job Training Method and the Employee Off-The-Job Training Method. Keywords: Human Resource Development, On The Job Training Method, Off The Job Training Method